Avaliação da resposta inflamatória local e sistêmica em modelo experimental de cisticercose subcutânea por Taenia crassiceps nas linhagens BALB/c convencional e deficiente para o gene de IL-4 - Lima, Sarah Buzaim (2014)
The parasitary diseases which are considered endemic in developing countries are a relevant public health problem. Around 50 million people in the world are infected by the teniasis-cysticercosis complex. Therefore, biological factors involved in the host susceptibility to parasitary diseases should be investigated due to the relevance of these infections in public health both in Brazil and in the world. As demonstrated by the literature, Interleukin-4, the main Th2 cytokine, has an important role in the immune response against parasites. The aim of this study was to evaluate the role of this cytokine in the subcutaneous cysticercosis pathogenesis through the comparison of the inflammatory responses in conventional BALB/C mice infection and in Interleukin-4 deficient BALB/C mice (IL-4 KO). An experimental model of subcutaneous infection with Taenia crassiceps cysticerci was used and macroscopic and microscopic parameters of the injury, cytokines profiles in splenocytes cultures from the infected animals from both types of BALB/c mice were evaluated to compare the local and systemic inflammatory response to the infection. During the experimental days the development of the chronic granulomatous inflammatory response was observed in the conventional animals with presence of macrophagic and lymphoplasmocytic inflammatory infiltrate and in the IL-4-KO animals with macrophages and polymorphonuclear cells in the inflammatory infiltrate. Conventional animals presented a mixed immune response pattern with an initial increase of IFNγ, which a Th1 cytokine, and evolved to chronicity with predominance of Th2 response and presence of IL-10 which modulates the immune response and favors the parasite infection. In the IL-4-KO animals it was possible to observe a partial destruction of the parasites in the first days of infection with increase in the Interferon gamma (IFNγ) production which is part of a Th1 accentuated response also the co-expression of IL-10 in these animals inhibited the accentuated Th1 response and contributed to the persistence of the infection. Fibrosis and tissue repair were not compromised in these animals. Furthermore, infected IL-4-KO animals presented a spontaneous production of IL-13 in higher concentrations than the conventional animals at 30 days of infection which contributed to the role of the Th2 immune response against the infection. The IL-4 deficiency directed the inflammation towards a greater microbicidal potential, partial destruction of the parasites in the first days of infection and significant reduction of eosinophils.